Parents' causal attributions and adjustment to their child's disability - Leskinen, Markku (1994)
The aim of this study was to examine how parents of children with severe disabilities explain and interpret causes for their child's disability. The hypothesis was that such explanations are important to parents and may have long-term effects on their child-related perceptions and adjustment. The tested model was created based on the principles of attributional theory by Weiner (1986). In the model, parents' current child-related feelings of guilt, other-blame, and hope were explained by their onset perceptions for the child's disability, and the feelings were hypothesized to predict their adjustment to the child's disability. The participants were 111 Finnish families, all of whom were entitled to the highest child care subsidy from the Social Insurance Institution at the time of the study. Children had various forms of developmental problems which their physicians had estimated to be severe enough to meet the criteria for the subsidy. The age of children ranged from 2 to 8 years. The mean age of fathers was 36.18, and for mothers' it was 34.55. The results from a path model testing supported the theorized model. It was supported better by the mothers' data; the fathers' other-directed perceptions were not statistically significant predictors. Those parents, who blamed themselves or others for the child's disability, reported to have more often feelings of guilt and other-blame relating to the child's disability. The more often the parents' experienced the feelings of guilt and other-blame, the lower was their adjustment. The higher the parents set the expectancy of the child's developmental progress, the more often they had feelings of hope, which predicted better adjustment. The results suggest, that parents' interpretations of their own or others' responsibility of the causes for their child's disability may have long term negative influences on their later adjustment. These parents seemed to interpret more often other child-related events by using the same blaming causal schemata.